Pengaruh Pajak Penjualan PPN Dan PPnBM Terhadap Laba Rugi Fiskal Pada UD Gemah Ripah - Viola Ardhana; Khasanah Sahara; Imarotus Suaidah (STIKes Ibnu Sina Ajibarang, 2023)
Taxes are a very important source for a sector of state revenue. To further increase revenue in the tax sector, several improvements have been made. In this research, the researcher tries to discuss the above problems related to